Representation of Race and Sex in Sleep Surgery Studies. (29th March 2022) - Debbaneh, Peter; Ramirez, Kimberly; Block‐Wheeler, Nikolas; Durr, Megan
Abstract : Objective: Obstructive sleep apnea (OSA) is a highly prevalent disorder with many treatment modalities, including surgical intervention. While OSA is known to be more prevalent in males and Black Americans, the representation of race and sex in sleep surgery studies is unknown. The aim of this systematic review is to assess the race and sex demographics represented in sleep surgery studies relative to known OSA demographics. Data Sources: PubMed, MEDLINE, and OVID databases. Review Methods: A systematic review was conducted to identify studies published between 2016 and 2020 that investigated sleep outcomes following nonnasal surgical intervention for OSA in adults. Pooled racial, ethnic, and sex data of the enrolled subjects in selected studies were analyzed. Results: The 148 included studies comprised 13, 078 patients. Of the 137 studies that reported sex, 84.0% of participants were male, exceeding the population prevalence of OSA in males, which is estimated at 66%. Only 13 studies reported racial/ethnic demographic data. Of these, 87.8% of patients were White. Out of 30 studies of primarily American patients, only 4 reported race demographic data, with an average of 82.8% White participants. Conclusion: There is a racial/ethnic and sex inclusion bias among sleep surgery studies. Future studies should better document the demographics of enrolled participants as well as recruit participants who better represent the demographics of adults with OSA in the general population.